Regulation of Renal Differentiation by Trophic Factors - Kurtzeborn, Kristen; Cebrian, Cristina; Kuure, Satu (Frontiers in Physiology, 2018)
Classically, trophic factors are considered as proteins which support neurons in their growth, survival, and differentiation. However, most neurotrophic factors also have important functions outside of the nervous system. Especially essential renal growth and differentiation regulators are glial cell line-derived neurotrophic factor (GDNF), bone morphogenetic proteins (BMPs), and fibroblast growth factors (FGFs). Here we discuss how trophic factor-induced signaling contributes to the control of ureteric bud branching morphogenesis and to maintenance and differentiation of nephrogenic mesenchyme in embryonic kidney. The review includes recent advances in trophic factor functions during the guidance of branching morphogenesis and self-renewal versus differentiation decisions, both of which dictate the control of kidney size and nephron number. Creative utilization of current information may help better recapitulate renal differentiation in vitro, but it is obvious that significantly more basic knowledge is needed for development of regeneration-based renal therapies.